Tá rindo do que? O funcionamento enunciativo do humor: polissemia e coexistência de sentidos n'o Pasquim - Dagneze, Cinara Sabadin (2018)
This thesis is initially intended to understand humor under different theoretical approaches. For this, it starts from the knowledge that the humor phenomenon has been, for a long time, the basis of the curiosity and studies of different thinkers. We resort to the studies of Georges Minois (2003), Henri Bergson (1940, 2007), Vladimir Propp (1992) and Sigmund Freud (1905/1977, 1928/2016), which allow us to trace a historical, philosophical, anthropological, cultural and psychoanalitic course of humor. The choice of these authors, in particular, is justified because somehow these theorists relate the functioning of humor and laughter to the human, to the social and, therefore, to the language and its meanings, what allows us to see, in their studies, an intimate relationship with the enunciative functioning of humor. This way, within their field of study, to some extent, all of them conceive language and its meanings as an important reference in the constitution of humor. From the appropriation of these conceptions, the Theory of Enunciation is used to propose a reflection on how this humor is constituted in the language and by the language, when, through the system, the subject manipulates and appropriates the whole language. We seek to understand how the categories of person and (inter)subjectivity mark the constitution of the speaker as subject, from the establishment of a you. This you, in the language appropriation movement, establishes itself as I and (re)means. Our methodological process starts from the appropriation of the enunciative studies of Émile Benveniste and his founding texts, so that this theoretical apparatus bases the analysis of the chosen corpus, that is, humor contents of the alternative weekly O Pasquim in issues dated from the period in which Brazil was under the strongest dictatorship (1964-1985) known as The Led Years (1968-1972). The presentation of some backstage stories from the O Pasquim doesn't have a historical scope here, but a linguistic one, since this context, which we named “enunciation conditions”, is indispensable for the understanding of the analyzes made in the final chapter of this work. Supported in the Theory of enunciation, we have seen this humor in O Pasquim and realized the enunciative functioning of humor takes place from the coexistence of senses produced in different times and places, involving different people. The enunciative studies also allow us to perceive that only the one that enunciates is the I – and therefore produces meanings – and that the coexistence is an enunciative strategy from the I in the production of the humor statement. It is also evidenced that subjectivity does not induces humor but it is in the humor. In this course, this thesis aims to identify the links amongst humor and the weekly O Pasquim by the language – considering it as “the whole language” and observing what it represents – and the enunciation, based on the coexistence of meanings and polysemy. So, we dedicate ourselves to answer our title-question: What are you laughing at? based, for this, at the enunciative functioning of humor and the polysemy and coexistence of meaningsin O Pasquim.